ChemInform Abstract: Nano Copper and Cobalt Ferrites as Heterogeneous Catalysts for the One‐Pot Synthesis of 2, 4, 5‐Tri Substituted Imidazoles. Issue 22 (15th May 2015) - Sanasi, Paul Douglas; Santhipriya, D.; Ramesh, Y.; Kumar, M. Ravi; Swathi, B.; Rao, K. Jaya
Abstract: A simple one‐pot synthesis is presented for the synthesis of trisubstituted imidazoles using magnetic recyclable spinel nano copper and cobalt ferrites by the condensation of benzil, different aromatic aldehydes, and ammonium acetate in ethanol.